British Association of Urological Surgeons (BAUS) consensus document for the management of male genital emergencies ‐ testicular trauma. (10th April 2018) - Lucky, Marc; Brown, Gareth; Dorkin, Trevor; Pearcy, Richard; Shabbir, Majid; Shukla, Chitranjan J.; Rees, Rowland W.; Summerton, Duncan J.; Muneer, Asif; ,
Abstract : Male genital emergencies relating to the penis and scrotum are rare and require prompt investigation and surgical intervention. Clinicians are often unfamiliar with the management of these conditions and may not work in a specialist centre with on‐site expertise in genitourethral surgery. A series of consensus statements have been developed by an expert consensus comprising British Association of Urological Surgeons (BAUS) Section of Andrology and Genitourethral Surgery together with experts from units throughout the UK. Testicular trauma requires prompt investigation and treatment in order to prevent the development of subfertility or hypogonadism. This series of consensus statements provide guidance for UK practice.